2017
DOI: 10.3390/ph10010007
|View full text |Cite
|
Sign up to set email alerts
|

CK2—An Emerging Target for Neurological and Psychiatric Disorders

Abstract: Protein kinase CK2 has received a surge of attention in recent years due to the evidence of its overexpression in a variety of solid tumors and multiple myelomas as well as its participation in cell survival pathways. CK2 is also upregulated in the most prevalent and aggressive cancer of brain tissue, glioblastoma multiforme, and in preclinical models, pharmacological inhibition of the kinase has proven successful in reducing tumor size and animal mortality. CK2 is highly expressed in the mammalian brain and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 103 publications
(130 reference statements)
0
73
0
Order By: Relevance
“…Increased protein kinase CK2 activity has been associated with detrimental effects in protein homeostasis and neuroinflammation in different neurodegenerative diseases (Castello et al 2017) but its role in HD is still controversial (Gomez-Pastor et al 2017, Atwal et al 2011, Fan et al 2008b). To determine whether CK2α’ plays a negative role during HD pathogenesis we first evaluated the relationship between HTT aggregation, neuronal loss and CK2α’ level over time in the striatum of the heterozygous zQ175 mouse model (Menalled et al 2012b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased protein kinase CK2 activity has been associated with detrimental effects in protein homeostasis and neuroinflammation in different neurodegenerative diseases (Castello et al 2017) but its role in HD is still controversial (Gomez-Pastor et al 2017, Atwal et al 2011, Fan et al 2008b). To determine whether CK2α’ plays a negative role during HD pathogenesis we first evaluated the relationship between HTT aggregation, neuronal loss and CK2α’ level over time in the striatum of the heterozygous zQ175 mouse model (Menalled et al 2012b).…”
Section: Resultsmentioning
confidence: 99%
“…Protein kinase CK2 is at the crossroads between neuroinflammation, glial function and synaptic activity and has recently emerged as a potential therapeutic target in neurodegeneration (Castello et al 2017). Pharmacological inhibition of CK2 in cell cultures expressing amyloid beta (Aβ) reduced Aβ aggregation and the production of pro-inflammatory cytokines and increased cell viability (Rosenberger et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The strong effect of the presence of DIA1 on CK2 phosphosites is interesting in the context of CK2 roles in the development of the nervous system and its status as a promising neurological drug target ( Castello et al, 2017 ; Litchfield, 2003 ). However, it cannot be ruled out that the observed changes in CK2 sites are partly due to activities of other kinases.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is implicated in cardiovascular pathology, cerebral hypoxia, and neurodegeneration, including Alzheimer's disease [8]. CK2 also contributes to the development of tumour, neoplastic cell proliferation and suppression of apoptosis, and it is overexpressed in various types of cancers, including human glioblastoma [7,13,14,33]. Studies have shown that an abnormally elevated CK2 level is required for tumour progression due to its role in the regulation of almost all the processes essential for cancer development, including suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%